Analisis Ketidaktepatan Kode Diagnosa Kasus Perinatal Rawat Inap di Rumah Sakit Nur Hidayah Bantul - Hery Setiyawan; Vidya Widowati; Carissa Maharani Istu Putri (Medika Promkes : Jurnal Kreativitas Kesehatan, 2026)
Background: The accuracy of diagnosis codes significantly impacts morbidity statistics, epidemiological studies, and clinical decision-making. However, a preliminary study at Nur Hidayah Hospital, Bantul, showed that the rate of diagnosis code inaccuracy remained high, reaching 60% (6 out of 10 medical records), even though the treatment code inaccuracy was 0%. This study aimed to analyze the coding process, the percentage of accuracy, and the factors causing inaccurate diagnosis and treatment codes in perinatal inpatients at the hospital. Methods: This descriptive, qualitative, cross-sectional study was conducted in February–March 2025. Subjects included coding staff and the head of medical records (triangulation), with 26 medical records of perinatal inpatients from 2023–2024 as subjects. The coding process was conducted post-assembly and was regulated by the official SOP of Nur Hidayah Hospital. Results and Discussion: Implementation of inpatient perinatal case coding at Nur Hidayah Hospital, Bantul, is suboptimal in the diagnosis sector (inaccuracy reached 53.8%), although the treatment sector is very good (100% accuracy). This high rate of inaccurate diagnosis codes is rooted in a combination of internal management factors (People, Method, Money), including a lack of uniformity in staff competency and accuracy, a lack of support from specific coding procedures, and the hospital's failure to allocate a budget for capacity building (training). Conclusion: Perinatal case coding at Nur Hidayah Hospital, Bantul, is suboptimal, with a diagnosis code inaccuracy rate reaching 53.8%, despite 100% accuracy in the treatment codes. This problem is caused by factors such as People (staff have not been trained, are not thorough, and have different understandings of lead terms), Method (the new SOP regulates the technical aspects of the electronic ICD, not the coding method), and Money (a training budget exists but has not been realized).   Keywords: Coding Inaccuracy, Perinatal; Hospital.